Preparation method of switch type mesoporous carbon compound capable of intelligently releasing and slowly releasing anthocyanin
By modifying mesoporous carbon sphere carrier and phenolic acid modified ester bond 'switch' technology, the stability and delivery problems of anthocyanins in the body are solved, and the intelligent release and sustained release in the intestinal inflammation are achieved, which improves its biological Utilization and biological activity.
Patent Information
- Application Number
- CN202411394559.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-08
- Publication Date
- 2025-01-03
AI Technical Summary
Anthocyanins are susceptible to environmental factors during processing, resulting in a decrease in stability, affecting their absorption and utilization rate in the body, and require delivery of carriers at specific locations to exert biological activity. The prior art has not effectively solved this problem.
Modified mesoporous carbon spheres are used as carriers, and the ester bonds of phenolic acid and phenolic hydroxyl groups are connected as a 'switch' in the outer layer of mesoporous carbon, and anthocyanins are released by esterase and reactive oxygen species during intestinal inflammation in the body. Achieve intelligent release and sustained release.
It improves the processing stability and bioavailability of anthocyanins, realizes intelligent release and sustained release in intestinal inflammation sites, and enhances the delivery effect of its biologically active substances.
Smart Images

Figure HDA0005073397180000011 
Figure HDA0005073397180000012 
Figure HDA0005073397180000013
Abstract
Description
Technical Field
[0001] The invention relates to a method for preparing a switch-type mesoporous carbon composite for intelligent and sustained release of anthocyanins, belonging to the technical field of nano-delivery. Background Art
[0002] Anthocyanins are the main bioactive substances in blueberries and have multiple physiological functions such as antioxidant, anti-cancer, and anti-inflammatory. - Attack, resulting in the cleavage of the C ring and reduced stability. In the processing system, the color and structural stability of anthocyanins are affected by different factors, such as pH, temperature, light, oxygen and the presence of other substances (including metal ions, carbohydrates, proteins and sulfur dioxide), which aggravate the degree of damage to anthocyanins during processing, resulting in poor product quality, which in turn affects the absorption and utilization rate in the body. And when absorbed and utilized orally, anthocyanins urgently need a carrier to deliver them to a specific location in order to better exert their biological activity.
[0003] Mesoporous carbon materials are a new type of non-silicon mesoporous materials discovered in recent years. The pore size range is (2 to 50 nm) and has received great attention and research. Mesoporous carbon has been proven to effectively increase drug loading and has good application prospects in biomedicine, such as drug delivery, gene transfection, photothermal therapy, photodynamic therapy, biosensors and other fields. This is mainly due to its advantages of high specific surface area, large pore volume, adjustable pore size, orderly open mesoporous structure and easy surface modification. It also has high corrosion resistance, good thermal stability and mechanical stability. Therefore, the preparation and application of mesoporous carbon spheres have become a hot topic in the field of materials research in recent years. Due to its unique properties and surface functionalization characteristics, it can adsorb relatively more compounds and ensure that the compounds are not destroyed by the external environment. Mesoporous carbon spheres show great potential in drug delivery and are used in various fields of biomedicine.
[0004] Mesoporous carbon is often used as a drug carrier to achieve the purpose of delivering drugs to the desired tissues, organs, cells and subcellular organs. It can effectively improve the pharmacological activity of therapeutic drugs, reduce drug toxicity and side effects, and overcome the problems of limited drug solubility and low bioavailability. The present invention uses the clinical drug dopamine hydrochloride and the food raw material chitosan oligosaccharide as carbon precursors, which are green, environmentally friendly, safe and non-toxic. The research and development of mesoporous carriers as drug delivery systems will provide more effective and feasible treatment technology prospects. Summary of the invention
[0005] The purpose of the present invention is to select safe and non-toxic raw materials to prepare oral drug delivery carriers, and provide a method for preparing a switch-type mesoporous carbon composite for intelligent release and sustained release of anthocyanins. The prepared mesoporous carbon spheres have good morphology and uniform size, and will be used for the intelligent delivery of compounds such as anthocyanins. The method of the present invention is simple, the raw materials are easily available, and the cost is low. The obtained product has a high yield, good product dispersibility, a significant mesoporous structure, and stable preparation. The prepared mesoporous carbon spheres have a good adsorption effect on anthocyanins. The outer carboxyl group of the modified mesoporous carbon is connected to the phenolic hydroxyl group of the phenolic acid through an ester bond, which serves as a "switch" for sealing the modified mesoporous carbon. When intestinal inflammation occurs in the body, due to the high expression of esterase and reactive oxygen, the "switch" is stimulated to open, and anthocyanins are released, thereby realizing the intelligent release and sustained release of anthocyanins delivered by mesoporous carbon at the site of intestinal inflammation.
[0006] The present invention utilizes modified mesoporous carbon to adsorb anthocyanins, and modifies different types of polyphenols on the outer layer. The outer carboxyl group of the modified mesoporous carbon is connected to the phenolic hydroxyl group of the phenolic acid through an ester bond, which serves as a "switch" to seal the mesoporous carbon. When intestinal inflammation occurs in the body, due to the high expression of esterase and reactive oxygen, the "switch" is stimulated to open, releasing anthocyanins, thereby achieving the intelligent release and sustained release of anthocyanins delivered by mesoporous carbon at the site of intestinal inflammation. Currently, there is no application in the delivery of anthocyanins. The present invention theoretically explores the protection of mesoporous carbon carriers on the processing homeostasis and oral absorption and utilization of anthocyanins, providing a theoretical basis for the delivery of functional active substances.
[0007] The invention provides a method for preparing a switch-type mesoporous carbon composite for intelligent and sustained release of anthocyanins.
[0008] A method for preparing a switchable mesoporous carbon composite for intelligent and sustained release of anthocyanins, wherein anthocyanins are loaded on modified mesoporous carbon containing carboxyl groups as a carrier, specifically: the inner layer of the modified mesoporous carbon containing carboxyl groups is modified with soybean lecithin and then loaded with anthocyanins, and then the outer layer of the mesoporous carbon loaded with anthocyanins is modified with phenolic acids having different numbers of phenolic hydroxyl groups, to obtain a switchable mesoporous carbon composite for intelligent and sustained release of anthocyanins.
[0009] In the above technical scheme, the modified mesoporous carbon containing carboxyl groups is prepared according to the following method: solid silica spheres are used as templates, dopamine hydrochloride and chitosan oligosaccharides are used as carbon sources, the carbon source is wrapped on the entire silica sphere, ammonia water is added after sufficient stirring and dissolution, a carbon-silicon complex is obtained, and then high-temperature carbonization is performed; HF is used to remove the solid silica spheres inside to obtain a hollow mesoporous carbon (HMC) carrier; the hollow mesoporous carbon carrier is modified using ammonium persulfate and concentrated sulfuric acid solution to obtain modified mesoporous carbon containing carboxyl groups.
[0010] Furthermore, the modified mesoporous carbon containing carboxyl groups is prepared by the following method:
[0011] S1, preparation of solid silica spheres: anhydrous ethanol, distilled water and ammonia water were mixed in a volume ratio of 42.8:6:1, and then an equal volume of ethyl orthosilicate was added dropwise to the ammonia water, stirred for a certain period of time, centrifuged, and the precipitate obtained was solid silica spheres, which were washed and dried;
[0012] S2, preparation of hollow mesoporous carbon carrier: solid silica spheres are dispersed in 50% ethanol aqueous solution, dopamine hydrochloride and chitosan oligosaccharide are added, ammonia water is added after sufficient stirring to dissolve, and the mixture is stirred at 30°C for 12 hours. The product is washed with water and ethanol and then dried, and carbonized at 400°C to 800°C for 2 hours under nitrogen protection; the hollow mesoporous carbon carrier is dispersed in 5% HF solution to remove the template for 12 hours to obtain a hollow mesoporous carbon carrier;
[0013] S3, preparation of modified mesoporous carbon containing carboxyl groups: the hollow mesoporous carbon carrier is modified by using 0.5 mol / L to 1 mol / L ammonium persulfate and 0.4 to 0.5 mol / L concentrated sulfuric acid solution to obtain modified mesoporous carbon containing carboxyl groups.
[0014] In the above technical solution, in step S2, the concentration of the solid silica spheres in the 50% ethanol aqueous solution is 0.5 mg / mL.
[0015] In the above technical solution, in step S2, the volume ratio of ammonia water to 50% ethanol aqueous solution is 0.075:2.
[0016] In the above technical scheme, soybean lecithin is dissolved in 70% ethanol aqueous solution to prepare a 0.5 mg / mL soybean lecithin solution, and the modified mesoporous carbon containing carboxyl groups is placed therein, stirred evenly, ultrasonicated, and centrifuged to obtain the mesoporous carbon with an inner layer modified with soybean lecithin, and the mass ratio of mesoporous carbon to soybean lecithin is 4:1.
[0017] Furthermore, the mesoporous carbon with an inner layer modified with soybean lecithin is added to the anthocyanin solution, the mass ratio of the carrier to the anthocyanin is 2:0.5-2.5, the mixture is evenly mixed, and magnetic stirring is carried out overnight. The magnetic stirring rate is 500-800 r / min, and the stirring time is 8-10 hours. The blueberry anthocyanin solution is an acidic solution of blueberry anthocyanin, and the concentration of the anthocyanin solution is 0.5-2.5 mg / mL; the acidic solution is a dilute hydrochloric acid aqueous solution with a pH of 3.0.
[0018] Furthermore, phenolic acid was added to the mesoporous carbon solution loaded with anthocyanins and stirred for 1 hour. The mass ratio of soybean lecithin: anthocyanin: mesoporous carbon: phenolic acid in the final system was 1:2:4:6. Centrifugation was performed, and the precipitate was taken and washed 2 to 3 times to obtain a switch-type mesoporous carbon composite with intelligent release and sustained release of anthocyanins.
[0019] Furthermore, the phenolic acid is one of tannic acid, catechin, and epigallocatechin gallate.
[0020] In the above technical scheme, the molar ratio of chitosan oligosaccharide to dopamine hydrochloride is 1:0 to 1:2, excluding 0.
[0021] In the above technical solution, the carbon source is added at room temperature, and the mass ratio of solid silica to the carbon source is 1:1.5.
[0022] The beneficial effects of the present invention are as follows: the present invention uses solid mesoporous silicon as a template, and selects clinical drug dopamine hydrochloride and food raw material chitosan oligosaccharide as carbon precursors, which are green, environmentally friendly, safe and non-toxic, with a simple preparation method, cheap and readily available raw materials, and suitable for scale-up production. The hollow mesoporous carbon spheres disclosed in the present invention, whose particle size, cavity size, mesoporous shell thickness and mesoporous pore size can all be regulated by changing the multi-component co-assembly and sol-gel conditions; the hollow mesoporous carbon spheres disclosed in the present invention, whose mesoporous pore size, specific surface area and pore volume can all be regulated by calcination conditions; the hollow mesoporous carbon spheres disclosed in the present invention have the advantages of the synergistic effect of mesoporous channels and cavities, and can collect anthocyanins in the hollow structure, which can slow down the decomposition of anthocyanins by digestive juices. The present invention uses mesoporous carbon as a delivery carrier for anthocyanins, which is green, environmentally friendly, safe and non-toxic, with a simple preparation method, cheap and readily available raw materials, and suitable for scale-up production. The anthocyanin delivery system disclosed in the present invention has a high encapsulation rate and loading rate for anthocyanins, thereby improving the processing stability and bioavailability thereof, and the complex has the effects of intelligent response and sustained release at the site of enteritis. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 Transmission electron microscopy images of hollow mesoporous carbon materials with different molar ratios of chitosan oligosaccharides and dopamine hydrochloride provided in Example 1 of the present invention; as shown in the transmission electron microscopy results, chitosan oligosaccharides alone cannot be coated on the surface of solid silica to form a continuous and stable carbon skeleton. When chitosan oligosaccharides and dopamine hydrochloride are in a 1:1 ratio, the morphology is not good. When chitosan oligosaccharides and dopamine hydrochloride are added in a 1:1 and 1:2 ratio, there is no obvious difference. In order to increase the proportion of chitosan oligosaccharides as much as possible, a 1:1 ratio of dopamine hydrochloride is selected for subsequent preparation.
[0024] Figure 2 Transmission electron microscopy morphology images of the carriers of the hollow mesoporous carbon materials provided in Examples 2, 3 and 4 of the present invention after carbonization at 400, 600 and 800° C., respectively; transmission electron microscopy shows that different carbonization temperatures have no obvious effect on the morphology of the hollow mesoporous carbon.
[0025] Figure 3The morphology of the hollow mesoporous carbon material carrier provided in Examples 2, 3 and 4 of the present invention is characterized by scanning electron microscopy after carbonization at 400, 600 and 800°C respectively; the scanning electron microscope shows that different carbonization temperatures have no obvious effect on the morphology of the hollow mesoporous carbon.
[0026] Figure 4 The specific surface area of the hollow mesoporous carbon material carrier provided in Examples 2, 3 and 4 of the present invention is characterized by nitrogen adsorption-desorption after carbonization at 400, 600 and 800°C respectively; the nitrogen adsorption-desorption isotherm of the hollow mesoporous carbon shows a typical Langmuir IV type adsorption curve, indicating that it has a mesoporous structure and an H1 type back ring appears, which means that the pore size of the mesoporous carbon nanoparticles is relatively uniform.
[0027] Figure 5 The particle size and potential diagram of the hollow mesoporous carbon material provided in Example 4 of the present invention; the particle size and potential diagram of the carrier after carbonization at 400, 600 and 800°C. The hydrated particle size of the carrier is about 240nm, the PDI is less than 0.3, and the dispersibility is good. The potential is about -22mV.
[0028] Figure 6 (A) to (C) are respectively the encapsulation efficiency and drug loading results of anthocyanin @ modified mesoporous carbon @ tannic acid / catechin / epigallocatechin gallate in Example 1 of the present invention; the results show that the encapsulation efficiency and drug loading are optimal when phenolic acid is 3 mg / mL, and the encapsulation efficiency and drug loading of tannic acid as a "switch" are the highest.
[0029] Figure 7 This is a graph showing the pH stability results of anthocyanin carriers coated with different phenolic acids in Example 1 of the present invention; tannic acid has the best controlled release effect as a "switch" and its stability protection effect is better than that of other phenolic acids.
[0030] Figure 8 This is a diagram showing the in vitro simulated digestion results of the tannic acid-coated anthocyanin carrier in Example 1 of the present invention; the tannic acid-coated anthocyanin carrier has a significant ability to resist erosion by digestive fluid compared to anthocyanins alone.
[0031] Fig. 9 This is a diagram showing the drug release results of the tannic acid-coated anthocyanin carrier in Example 1 of the present invention; the drug release rate of the tannic acid-coated anthocyanin carrier is slower than that of anthocyanin alone, and when stimulated by esterase, anthocyanin is released rapidly, indicating that the carrier has a certain responsiveness to esterase. DETAILED DESCRIPTION
[0032] The following non-limiting embodiments may enable a person skilled in the art to more fully understand the present invention, but are not intended to limit the present invention in any way.
[0033] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0034] One of the specific implementations:
[0035] The method provided by the present invention first prepares a solid silica ball as a hard template for the subsequent preparation of mesoporous carbon. Secondly, a carbon-silicon composite is prepared, wherein chitosan oligosaccharide and dopamine hydrochloride are used as carbon sources and the solid silica ball is used as a template. Finally, the silica template is removed by a hydrofluoric acid (HF) solution to obtain a hollow mesoporous carbon material with a high surface area, a large pore volume and an adjustable pore size. In order to improve the dispersibility of the carrier, the carrier is carboxyl-modified by an oxidation method.
[0036] The mesoporous carbon spheres prepared by the preparation method of the present invention use chitosan oligosaccharides from food sources as carbon precursors, which are cheap and easy to obtain, and use dopamine hydrochloride, a mussel-like byssus material, which has rich catechol structures and amino groups and can be combined with each other or with the hydroxyl groups of other molecules in the form of van der Waals forces, hydrogen bonds and π-π interactions. After the introduction of dopamine hydrochloride, it can interact with chitosan oligosaccharides and the hydroxyl groups on the surface of solid silica, forming a network structure coated on the surface of solid silica in a hand-in-hand manner. In order to adsorb anthocyanins, the mesoporous carbon is modified with carboxyl groups on the outside to increase hydrophilicity, and soybean lecithin is modified on the inside to increase the hydrophilicity and lipophilicity of anthocyanins, and the carboxyl groups on the surface of the mesoporous carbon are connected with the phenolic hydroxyl groups of phenolic acid by ester bonds, so that when esterase and ROS are upregulated at the inflammation site, the ester bonds are broken, so that it has the effect of efficient delivery, intelligent release and sustained release of anthocyanins. The mesoporous carbon carrier prepared by the present invention can realize the oral delivery of functional active substances and the intelligent release and sustained release of enteritis sites.
[0037] A method for preparing a switchable mesoporous carbon composite for intelligent and sustained release of anthocyanins comprises the following steps:
[0038] 1. Preparation of solid silica spheres: add anhydrous ethanol, distilled water and ammonia water to a conical flask in turn, stir magnetically at a certain temperature until the mixture is evenly mixed. Then add the silicon source precursor dropwise, stir for a certain period of time, centrifuge, and the precipitate is the solid silica sphere. The solid silica sphere is washed with distilled water and anhydrous ethanol for later use, and after drying, it is the solid silica hard template.
[0039] 2. Preparation of carbon-silicon composite: Re-disperse a certain amount of solid silica spheres in a mixed solution of ethanol and water, add carbon sources of different molar ratios, stir, and add ammonia water after sufficient stirring and dissolution, and stir at 30°C for 12 hours. The product is washed twice with water and ethanol respectively, and then fully dried, and carbonized at high temperature under nitrogen protection.
[0040] 3. Preparation of hollow mesoporous carbon: Use HF aqueous solution to remove the internal silica, collect the precipitate, and dry it to obtain a hollow carbon carrier.
[0041] 4. Modification of hollow mesoporous carbon: The hollow mesoporous carbon carrier is modified by using ammonium persulfate and concentrated sulfuric acid solution to obtain modified mesoporous carbon containing carboxyl groups.
[0042] 5. Loading of anthocyanins: Dissolve soybean lecithin in an ethanol aqueous solution, place mesoporous carbon therein, stir evenly, ultrasonicate, and centrifuge to obtain mesoporous carbon with inner layer modified with soybean lecithin. Add the mesoporous carbon with inner layer modified with soybean lecithin to the anthocyanin solution, mix evenly, and stir magnetically overnight. The magnetic stirring rate is 500-800r / min, and the stirring time is 8-10h. The blueberry anthocyanin solution is an acidic solution of blueberry anthocyanin, and the concentration of the anthocyanin solution is 0.5-2.5mg / mL; the acidic solution is a dilute hydrochloric acid aqueous solution with a pH of 3.0. Add phenolic acid to the mesoporous carbon solution loaded with anthocyanin, stir for 1h, and the mass ratio of soybean lecithin: anthocyanin: mesoporous carbon: phenolic acid in the final system is 1:2:4:6. Centrifuge, take the precipitate, wash 2-3 times, and obtain the loaded anthocyanin complex.
[0043] In the above step 2, dopamine hydrochloride and chitosan oligosaccharide are used as carbon sources, and the solution thereof is stirred at room temperature for 6 to 12 hours, and the solvent is selected from at least one of water, ethanol and methanol.
[0044] In the above step 2, the precipitate is placed in an oven, the oven temperature should be 50-60°C, and the drying time is 8-12 hours.
[0045] In the above step 2, the temperature in the vacuum tube furnace is raised to 750° C. to 850° C. at a rate of 5 to 10° C. / min.
[0046] In the above step 3, the concentration of the HF solution is 5wt%.
[0047] In the above step 5, the blueberry anthocyanin solution is an acidic ethanol solution of blueberry anthocyanins, and the anthocyanin concentration is 0.5 to 2.5 mg / mL.
[0048] In the above step 5, the acidic solution is a dilute hydrochloric acid aqueous solution with a pH of 3.0.
[0049] In the above step 5, the blueberry anthocyanin solution is sonicated for 5 to 10 minutes and is prepared before use.
[0050] In the above step 5, the mass ratio of soybean lecithin to modified mesoporous carbon is 1:4.
[0051] In the above step 5, the mass ratio of the blueberry anthocyanin to the modified mesoporous carbon is 1:2.
[0052] In the above step 5, the phenolic acid is one of tannic acid, catechin, and epigallocatechin gallate.
[0053] In the above step 5, the mass ratio of the modified mesoporous carbon to the outer layer modified phenolic acid is 1:1-3.
[0054] In the above step 5, the magnetic stirring rate is 500-800 r / min, and the stirring time is 8-10 h.
[0055] In the above step 5, the raw material used for modifying the outer layer of the mesoporous carbon is one of tannic acid, catechin, and epigallocatechin gallate.
[0056] Example 1
[0057] Preparation of solid silica spheres: 428 mL ethanol, 10 mL ammonia water and 60 mL water, set the magnetic stirrer to 30 ° C, stir at 600 rpm for 15 min. Add 10 mL of ethyl orthosilicate under stirring conditions. After stirring for 2 hours, centrifuge (12000 rpm, 15 min) to collect and wash with water 3 times, and dry to obtain a solid silica hard template.
[0058] Preparation of carbon-silicon composite: Weigh the solid silica (100 mg) prepared above and ultrasonically disperse it into 20 mL of 50% ethanol aqueous solution. Add a carbon source at room temperature. The mass ratio of solid silica to carbon source is 1:1.5. The carbon source is a complex of chitosan oligosaccharide and dopamine hydrochloride, and the molar ratio of the two is 1:0.5, 1:1, and 1:2. After fully stirring and dissolving, add 0.75 mL of ammonia water and stir at 30 ° C for 12 hours. The product is washed twice with water and ethanol respectively, then fully dried and carbonized at 800 ° C for 2 hours under nitrogen protection. After completion, disperse it in 5% HF to remove the template for 12 hours to obtain hollow mesoporous carbon. Wash with water to remove HF and store.
[0059] Carboxylation modification of hollow mesoporous carbon: prepare a 0.5 mol / L ammonium persulfate (APS) solution, place 12 mL of the solution in a 25°C water bath, and add 0.3 mL of concentrated sulfuric acid while stirring. Add 100 mg of hollow mesoporous carbon, heat to 60°C in a water bath and reflux for 3 h, centrifuge (10000 rpm, 10 min) after the temperature drops to room temperature, wash the precipitate with distilled water and anhydrous ethanol, respectively, and dry the carboxylation-modified mesoporous carbon.
[0060] Loading of anthocyanins: Dissolve 20 mg of soybean lecithin in 40 mL of 70% ethanol solution, vortex until dissolved, weigh 80 mg of modified mesoporous carbon containing carboxyl groups and add it, stir magnetically for 30 minutes, ultrasonically probe for 3 minutes, centrifuge, take the precipitate, and dissolve 40 mg of blueberry anthocyanins in 40 mL of pH 3.0 hydrochloric acid solution. Add the anthocyanin solution to the mesoporous carbon so that the mass ratio of anthocyanin to modified mesoporous carbon containing carboxyl groups is 1:2, stir magnetically for 10 hours, and the stirring rate is 600r / min to obtain a mesoporous carbon-anthocyanin mixed solution. Weigh one of tannic acid, catechin, and epigallocatechin gallate and add it so that the mass ratio of phenolic acid to modified mesoporous carbon is 1:1, 2:1, 3:1, and 4:1, respectively. The magnetic stirring rate is 600r / min, and the stirring time is 30min to obtain an anthocyanin solution coated with phenolic acid and HMC. The mixture was centrifuged at 8000 rpm for 15 min and washed three times to obtain a switchable mesoporous carbon composite with intelligent release and sustained release of anthocyanins.
[0061] Determination of encapsulation efficiency and drug loading: The ratio of the mass of anthocyanins loaded to the mass of anthocyanins initially added is the encapsulation efficiency; the ratio of the mass of anthocyanins loaded to the mass of the total drug added is the drug loading.
[0062] Processing stability determination: The complex was redissolved in solutions of pH 2, 4, and 6 and stored at room temperature for 48 hours to test the processing stability.
[0063] In vitro simulated digestion stability: The complex was redissolved in a pH 3.0 solution and its stability in simulated gastrointestinal digestive fluid was determined.
[0064] Drug release: The nanoparticles were redissolved in a solution of pH 3.0 and placed in a 3500Da dialysis bag. Simulated gastrointestinal digestive fluid was added to the outside of the dialysis bag, and samples were taken at regular intervals to determine the anthocyanin release rate.
[0065] Example 2
[0066] Preparation of solid silica spheres: Same as Example 1
[0067] Preparation of carbon-silicon composite: Weigh the solid silica prepared above and ultrasonically disperse it into 10 mL of ethanol and 10 mL of water. Add a carbon source at room temperature. The mass ratio of solid silica to carbon source is 1:1.5, and the carbon source is a complex of chitosan oligosaccharide and dopamine hydrochloride, with a molar ratio of 1:1. After fully stirring and dissolving, add 0.75 mL of ammonia water and stir at 30 ° C for 12 hours. The product is washed twice with water and ethanol respectively, then fully dried and carbonized at 400 ° C for 2 hours under nitrogen protection. After completion, disperse it in 5% HF to remove the template for 12 hours to obtain HMC. Wash with water to remove HF and store.
[0068] Carboxylation modification of hollow mesoporous carbon: same as Example 1
[0069] Anthocyanin loading: Same as Example 1
[0070] Example 3
[0071] Preparation of solid silica spheres: Same as Example 1
[0072] Preparation of carbon-silicon composite: Preparation of carbon-silicon composite: Weigh the solid silica prepared above and ultrasonically disperse it into 10mL ethanol and 10mL water, add carbon source at room temperature, the mass ratio of solid silica and carbon source is 1:1.5, and the carbon source is a complex of chitosan oligosaccharide and dopamine hydrochloride, the molar ratio of the two is 1:1. After fully stirring and dissolving, add 0.75mL ammonia water and stir at 30℃ for 12h. The product is washed twice with water and ethanol respectively, then fully dried and carbonized at 600℃ for 2h under nitrogen protection. After completion, disperse in 5% HF to remove the template for 12h to obtain hollow mesoporous carbon. Wash with water to remove HF and store.
[0073] Carboxylation modification of hollow mesoporous carbon: same as Example 1.
[0074] Anthocyanin loading: Same as Example 1
[0075] Example 4
[0076] Preparation of solid silica spheres: Same as Example 1
[0077] Preparation of carbon-silicon composite: Preparation of carbon-silicon composite: Weigh the solid silica prepared above and ultrasonically disperse it into 10mL ethanol and 10mL water, add carbon source at room temperature, the mass ratio of solid silica and carbon source is 1:1.5, and the carbon source is a complex of chitosan oligosaccharide and dopamine hydrochloride, the molar ratio of the two is 1:1. After fully stirring and dissolving, add 0.75mL ammonia water and stir at 30℃ for 12h. The product is washed twice with water and ethanol respectively, then fully dried and carbonized at 800℃ for 2h under nitrogen protection. After completion, disperse in 5% HF to remove the template for 12h to obtain hollow mesoporous carbon. Wash with water to remove HF and store.
[0078] Carboxylation modification of hollow mesoporous carbon: same as Example 1.
[0079] Anthocyanin loading: Same as Example 1.
Claims
1. A method for preparing a switchable mesoporous carbon composite for intelligent and sustained release of anthocyanins, characterized in that: Anthocyanins are loaded on modified mesoporous carbon containing carboxyl groups. Specifically, the inner layer of the modified mesoporous carbon containing carboxyl groups is modified with soybean lecithin and then loaded with anthocyanins. Then, the outer layer of the mesoporous carbon loaded with anthocyanins is modified with phenolic acids having different numbers of phenolic hydroxyl groups to obtain a switchable mesoporous carbon composite that can intelligently release and slowly release anthocyanins.
2. The method according to claim 1, characterized in that: The modified mesoporous carbon containing carboxyl groups is prepared according to the following method: solid silica balls are used as templates, dopamine hydrochloride and chitosan oligosaccharides are used as carbon sources, the carbon sources are wrapped on the entire silica balls, ammonia water is added after being fully stirred and dissolved to obtain a carbon-silicon composite, and then high-temperature carbonization is performed; hydrofluoric acid (HF) is used to remove the solid silica balls inside to obtain a hollow mesoporous carbon carrier; the hollow mesoporous carbon carrier is modified by ammonium persulfate and concentrated sulfuric acid solution to obtain a modified mesoporous carbon containing carboxyl groups.
3. The method according to claim 2, characterized in that The modified mesoporous carbon containing carboxyl groups is prepared by the following method: S1, preparation of solid silica spheres: anhydrous ethanol, distilled water and ammonia water were mixed in a volume ratio of 42.8:6:1, and then an equal volume of ethyl orthosilicate was added dropwise to the ammonia water, stirred for a certain period of time, centrifuged, and the precipitate obtained was solid silica spheres, which were washed and dried; S2, preparation of hollow mesoporous carbon carrier: solid silica spheres are dispersed in 50% ethanol aqueous solution, dopamine hydrochloride and chitosan oligosaccharide are added, ammonia water is added after sufficient stirring to dissolve, and the mixture is stirred at 30°C for 12 hours. The product is washed with water and ethanol and then dried, and carbonized at 400°C to 800°C for 2 hours under nitrogen protection; the hollow mesoporous carbon carrier is dispersed in 5% HF solution to remove the template for 12 hours to obtain a hollow mesoporous carbon carrier; S3, preparation of modified mesoporous carbon containing carboxyl groups: the hollow mesoporous carbon carrier is modified by using 0.5 mol / L to 1 mol / L ammonium persulfate and 0.4 to 0.5 mol / L concentrated sulfuric acid solution to obtain modified mesoporous carbon containing carboxyl groups.
4. The method according to claim 2 or 3, characterized in that: The molar ratio of chitosan oligosaccharide to dopamine hydrochloride is 1:0 to 1:2, excluding zero.
5. The method according to claim 2 or 3, characterized in that: The carbon source was added at room temperature, and the mass ratio of solid silica to the carbon source was 1:1.
5.
6. The method according to claim 1, characterized in that Soybean lecithin was dissolved in 70% ethanol aqueous solution to prepare a 0.5 mg / mL soybean lecithin solution, and the modified mesoporous carbon containing carboxyl groups was placed therein, stirred evenly, ultrasonicated, and centrifuged to obtain the mesoporous carbon with an inner layer modified with soybean lecithin, and the mass ratio of the mesoporous carbon to the soybean lecithin was 4:
1.
7. The method according to claim 6, characterized in that The mesoporous carbon with an inner layer modified with soybean lecithin is added to the anthocyanin solution, the mass ratio of the mesoporous carbon to the anthocyanin is 2:0.5-2.5, the mixture is evenly mixed, and magnetic stirring is carried out overnight. The magnetic stirring rate is 500-800 r / min, and the stirring time is 8-10 hours. The blueberry anthocyanin solution is an acidic solution of blueberry anthocyanin, and the concentration of the anthocyanin solution is 0.5-2.5 mg / mL; the acidic solution is a dilute hydrochloric acid aqueous solution with a pH of 3.
0.
8. The method according to claim 6, characterized in that Phenolic acid was added to the mesoporous carbon solution loaded with anthocyanins and stirred for 1 hour. The mass ratio of soybean lecithin: anthocyanin: mesoporous carbon: phenolic acid in the final system was 1:2:4:
6. Centrifugation was performed, and the precipitate was taken and washed 2 to 3 times to obtain a switch-type mesoporous carbon composite for intelligent release and sustained release of anthocyanins.